The combined effects of land use and seasonal environmental factors on stream food web structure - Wang, Yang; Li, Siyue; Tan, Xiang; Zhang, Quanfa (Frontiers in Environmental Science, 2022)
Land use and seasonal changes in environmental conditions influence biological communities and their trophic interactions in riverine ecosystems. However, how land use and the seasonality of environmental conditions jointly influence the food web structure of riverine ecosystems remains unclear. Here, we conducted a comparative study on basal resources, macroinvertebrates, and fish at woodland and urban sites to explore the combined effects of land use and environmental conditions during spring, autumn, and winter on the food web structure of a subtropical river in China. We used δ13C and δ15N to trace consumers’ diets and calculate community-level metrics within food webs. At woodland sites, we found that allochthonous sources contributed significantly more to consumers’ diets in the high flow season (53%) than in the low flow season (around 30%), but allochthonous sources contributed less than 30% at urban sites. The seasonal flooding facilitated the acquisition of terrestrial sources at woodland sites, while the impervious surface cover at urban sites cut off the influx of terrestrial inputs. The isotopic niche space of basal resources at both woodland and urban sites was significantly higher in the high flow season. However, the isotopic niche space of consumers at urban sites was not significantly different between seasons. Trophic length, niche width, and trophic redundancy showed no seasonal differences at urban sites, but trophic length increased significantly during the high flow season at woodland sites. Our temporal food web study at urban and woodland rivers illustrated the combined effects of land use and seasonal environmental conditions on the food web structure, and highlighted the role of allochthonous carbon in supporting biological communities and the importance of lateral and longitudinal connectivity in river ecosystems.